Maverick Rates and Application Timings for Weed Control in Kansas Corn - Patrick W. Geier; Sarah H. Lancaster (Kansas Agricultural Experiment Station Research Reports, 2025)
Maverick herbicide was evaluated as a preemergence (PRE) treatment at Manhattan, and as a PRE and postemergence (POST) treatment at Garden City. Early in the season, Maverick applied preemergence (PRE) was as effective as Bicep II Magnum, Harness Xtra, Verdict, Resicore, or Acuron for kochia, Palmer amaranth, and green foxtail control at Garden City. Maverick PRE also controlled Russian thistle 95% early. Later in the season, Maverick or Kyro postemergence (POST) provided at least 95% kochia control, 98% Palmer amaranth control, and complete Russian thistle and green foxtail control. At the Manhattan location, Maverick was as effective on Palmer amaranth as the competitive standards. Control of entireleaf morningglory and common sunflower were more variable, but Maverick controlled these species as well as the competitive standards. Herbicide treatment at Garden City increased grain yields 57% to 81% relative to the weedy controls.
Keywords: Sequential applications; residual control